Social Identity and HIV Stigma: A Phenomenological Study - Jafar Zolfali Fam; Mansour Mo'aghar; Zahra Samadnezhad Azar (Kerman University of Medical Sciences, 2021)
Introduction: The purpose of the present study was to explore how HIV stigma is constructed in the social relationships between healthy people and AIDS-affected people and how the social identity of those who suffer from it is stigmatized. Moreover, given the public negative assessment of AIDS that forms stigmatized and devalued identities for AIDS-affected people and their families, this study examined the impact of HIV stigma on the successes and opportunities of AIDS-affected people.Methods: This study employed a qualitative research method based on an empirical phenomenological approach. The data were collected using in-depth interviews and the interviewees were selected using purposive sampling. Accordingly, 15 AIDS-affected people living in Tabriz in 2017 were interviewed. The interviews were recorded, transcribed, and analyzed using Colaizzi's method.Results: The findings of this study indicated that AIDS-affected people use five main strategies to manage HIV-related stigmas in their social relations. These strategies include concealment, denial, social isolation, informed group membership, and normalization.Conclusion: The results revealed AIDS-affected people can continue their normal life and have relationships with healthy people by accepting the reality of their illness. However, the most frequently used strategy by AIDS-affected people to manage their social relationships is the denial of their disease when other people directly ask about it. Even in places such as barbers and hairdressing shops, dental clinics, and hospitals with the high possibility of infecting other people, AIDS-affected people are more likely to conceal their disease, contributing intentionally or unintentionally to spreading AIDS in the community.